Existence and Uniqueness of Solution for a Class of Nonlinear Degenerate Elliptic Equations (Analysis in Theory and Applications, 2022)
In this work we are interested in the existence and uniqueness of solutions for the Navier problem associated to the degenerate nonlinear elliptic equationsin the setting of the weighted Sobolev spaces.